Sosialisasi Manfaat Moda Transportasi Publik Berbasis Rel untuk Peningkatan Animo Penggunaan Kereta Api di Rute Maros-Barru Sulawesi Selatan - Ramli, Muhammad Isran; Adisasmita, Sakti Adji; Sabil, Muhammad Ikhsan; Yatmar, Hajriyanti; Tjaronge, Muhammad Wihardi; Bakri, Bambang; Hustim, Muralia; Aly, Sumarni Hamid; Tarakka, Rustan; Sirajuddin, Yahya; Chaerunnisa, Andi Sitti (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Maros-Barru railway is a strategic route to be developed as a public transportation mode that can connect two important areas in the province of South Sulawesi. However, even though the railway infrastructure in this area already exists, the level of train use by the community is still quite low. The demand for this travel need is significant for planning purposes, both facilities and infrastructure, especially transportation. The lack of public interest in trains on the Maros-Barru route is caused by several factors, one of which is the lack of information received by the community regarding the benefits and comfort offered by trains. Socialization of the benefits of rail-based public transportation will be carried out through various communication channels to reach more passengers, and it is hoped that this activity will benefit policymakers in the management and planning of trains in Sulawesi and reduce transportation problems. Before the socialization, there was no value, but after the socialization, a value of 2984 was obtained, which was in the range of 2501-3250, with the criteria Good. This means that this activity is also expected to be a preference for public transportation modes, especially trains, and the transition from other transportation modes to trains.